Sustainabnility of Product Market Collusion under Credit Market Imperfections - Sugata Marjit; Arijit Mukherjee; Lei Yang (Center for Economic Studies and ifo Institute (CESifo), 2016)
We study the implications of credit constraints for the sustainability of product market collusion in a bank-financed oligopoly in which firms face an imperfect credit market. We consider two situations, without and with credit rationing, i.e., with a binding credit limit. When there is credit rationing, a moderately higher cost of external financing may affect the degree of collusion, but a substantial increase keeps it unaffected relative to the no-constraint case. A permanent adverse demand shock in this setup does not affect the possibility of collusion, but may aggravate financing constraints and eventually lead to collusion. We consider both Cournot and Bertrand models, and the results are qualitatively the same.
Keywords: D21; D43; G21; 330; collusion; credit market; debt-equity